2014
DOI: 10.1245/s10434-014-3902-4
|View full text |Cite
|
Sign up to set email alerts
|

Does BMI Affect the Accuracy of Preoperative Axillary Ultrasound in Breast Cancer Patients?

Abstract: Despite theoretical concern regarding both potential technical challenges and obesity-related lymph node alterations, the sensitivity of preoperative AUS for detecting nodal metastasis was similar in obese and non-obese patients, while specificity was better in obese patients. Preoperative AUS is valuable for preoperative nodal staging of obese breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…We have previously demonstrated that the identification of abnormal nodes on preoperative imaging 22 or even a positive needle biopsy 23 does not reliably identify a group of patients who require ALND when ACOSOG Z0011 eligibility criteria are otherwise met. While BMI has been not been shown to impact the sensitivity of axillary ultrasound 24-26 , our data suggest that obesity itself is not an indication for additional axillary evaluation.…”
Section: Discussioncontrasting
confidence: 59%
“…We have previously demonstrated that the identification of abnormal nodes on preoperative imaging 22 or even a positive needle biopsy 23 does not reliably identify a group of patients who require ALND when ACOSOG Z0011 eligibility criteria are otherwise met. While BMI has been not been shown to impact the sensitivity of axillary ultrasound 24-26 , our data suggest that obesity itself is not an indication for additional axillary evaluation.…”
Section: Discussioncontrasting
confidence: 59%
“…The only patients fast tracked to ANC would be those patients with palpable axillary lymphadenopathy—consistent with the protocols of RCTs of SNB [ 5 10 ]. This approach would make a contribution, but may give the appearance of a regressive step and could be detrimental in patients with a high body mass index where axillary ultrasound has been demonstrated to possess great accuracy [ 25 ]. It is known that this approach to omitting pre-operative axillary ultrasound has already been adopted in certain academic breast units within the USA.…”
Section: Discussionmentioning
confidence: 99%
“…It has the ability to detect significant nodal disease. We have shown that this does not appear to be influenced by tumor histology nor by patient factors such as body mass index .…”
Section: Imaging Featuresmentioning
confidence: 73%